Effectiveness of perturbation training on contralateral knee joint to improve stability in anterior cruciate ligament deficient knee joint - R MANJULA,; A PAHINIAN,; G PREMKUMARI, (International Journal of Pharma and Bio Sciences, 2017)
Loss of stability is a very common problem in Anterior Cruciate Ligament Deficient (ACLD) knee. To evaluate the effectiveness of Perturbation training on ACLD knee joint and Contralateral knee joint compared with Perturbation training on the ACLD knee joint alone. Patients were randomized into two groups using a Pre/Post-test experimental design. On the day 0 and 28th (i.e. pre and post treatment)patients were administered Non-Weight Bearing proprioception questionnaire and Weight Bearing Postural Sway on single leg stance were completed using validated outcome measures. Both group were performed Perturbation training protocol for 10 sessions (2-3session per weeks) on ACLD knee joint additionally only one group performed Perturbation training on the Contralateral knee also. Chi-Square test was used to compare the Non-Weight Bearing proprioception questionnaire. Paired t-test and unpaired t-test were used to compare the Postural Sway on single leg stance with eyes open followed by eyes closed. The data showed that with the use of 10 sessions of Perturbation training protocol there is a significant difference between the post values of Postural Sway on single leg stance between group A and group B but more improvement was seen in group B i.e. significant difference inreduction of postural sway. The data of this study showed that there was non-significant difference between post values of Non-Weight Bearing proprioception questionnaire between group A and group B. This study concluded that the Perturbation training on the ACLD knee along with the contralateral kneejoint improve the Stability in ACLD knee and also improve the postural stability hence it reduces the risk of fall and re-occurrence of injury.